Методичний підхід до просування послуг на засадах економіки вражень (на прикладі послуг освітньої галузі) - Пушкар, Олександр Іванович; Курбатова (Татаринцева), Юлія Леонідівна (Інститут економіки та прогнозування НАН України, 2017)
Запропоновано методичний підхід щодо просування послуг на основі економіки вражень. Доведено, що конкурентні переваги при просуванні послуг має ВНЗ, реклама якого викликає емоції та справляє враження. Проведене емпіричне дослідження дозволило виявити особливості цільової аудиторії, що було враховано при розробці рекомендацій щодо плану просування ВНЗ. Обґрунтовано вибір сукупності інструментів просування послуг з урахуванням 4 сфер вражень: освіти, розваг, соціальної значущості, віртуальної реальності.

The methodical approach to advancement of services based on the experience economy is proposed. It is proved that the competitive advantages in the services promotion has the university, the advertising of which causes emotions and creates experience. The methodical approach involves the implementation of four stages: the first stage – the study of the target audience characteristics; the second stage is the selection of tools for the information environment where the services promotion is carried out; the third stage – the choice of set of tools for services promotion in the information environment with the impression of experiences and budget formation; the fourth stage is the feedback analysis. The conducted empirical research made it possible to reveal features of the target audience, in particular aesthetics, spirituality; the average level of preparation in computer sciences; average IQ level. This was taken into account while developing recommendations for a university promotion plan. To substantiate the choice of social networks, research was conducted on the presence and communication of the first year students in social networks and through mobile applications. A content plan for the promotion of educational services in social networks was developed on the example of the university under study. The choice of set of tools for services promotion is justified by taking into account the four spheres of experience: education, entertainment, social significance, virtual reality based on the experience generalization of advanced domestic and foreign universities and authors' own proposals. The aggregate of the promotion tools on the example of the university under study is divided into groups of online and offline environments. Special attention should be paid to the online environment, as it is the most popular and promising among the target audience. Making experiences when promoting services involves the use of as many areas of experience as possible, since this allows to achieve the best effect. Feedback analysis is carried out based on the processing of statistical data of analytical programs in social networks, conducting surveys, etc. The proposed methodological approach allows to promote educational services taking into account the emotional component of the content perception process by entrants. Based on the formation of experience and emotional response, advertising of high schools is perceived with great interest and the content is more likely to spread among the target audience.
Methodical approach to the promotion of services based on the experience economy (on the example of educational services)
Keywords: економіка вражень; просування послуг; освіта; інформаційне середовище; experience economy; promotion of services; education; information environment